DIGITAL ECONOMY AND AGRICULTURE - A. CH.Abdiyev (American Journals, 2023)
The article considers the state of development of agricultural production in the agricultural sector in the digital economy.
Keywords: Fund, natural resources, organizational-legal framework, management system, innovative technologies, investment